Hetero-site-specific X-ray pump-probe spectroscopy for femtosecond intramolecular dynamics - Picón, A.; Lehmann, C. S.; Bostedt, C.; Rudenko, A.; Marinelli, A.; Osipov, T.; Rolles, D.; Berrah, N.; Bomme, C.; Bucher, M.; Doumy, G.; Erk, B.; et al. (My University, 2016)
New capabilities at X-ray free-electron laser facilities allow the generation of two-colour femtosecond X-ray pulses, opening the possibility of performing ultrafast studies of X-ray-induced phenomena. Particularly, the experimental realization of hetero-site-specific X-ray-pump/X-ray-probe spectroscopy is of special interest, in which an X-ray pump pulse is absorbed at one site within a molecule and an X-ray probe pulse follows the X-ray-induced dynamics at another site within the same molecule. Here we show experimental evidence of a hetero-site pump-probe signal. By using two-colour 10-fs X-ray pulses, we are able to observe the femtosecond time dependence for the formation of F ions during the fragmentation of XeF2 molecules following X-ray absorption at the Xe site.